Strategies to Improve Enrollment and Participation in Pulmonary Rehabilitation Following a Hospitalization for COPD: RESULTS OF A NATIONAL SURVEY. Issue 3 (25th May 2023) - Kotejoshyer, Rajashree; Eve, Julianna; Priya, Aruna; Mazor, Kathleen; Spitzer, Kerry A.; Pekow, Penelope S.; Pack, Quinn R.; Lindenauer, Peter K.
Abstract : The chronic obstructive pulmonary disease (COPD) national action plan emphasizes the need to improve participation in pulmonary rehabilitation (PR). This study describes current practices used by PR programs in the United States to encourage participation in PR after a hospitalization for COPD and identifies opportunities to improve practice at the organization, provider, and patient level. Abstract : Purpose: Pulmonary rehabilitation (PR) improves outcomes for patients with chronic obstructive pulmonary disease (COPD); however, very few patients attend. We sought to describe strategies used to promote participation in PR after a hospitalization for COPD. Methods: A random sample of 323 United States based PR programs was surveyed. Using a positive deviance approach, a 39-item survey was developed based on interviews with clinicians at hospitals demonstrating high rates of participation in PR. Items focused on strategies used to promote participation as well as relevant contextual factors. Results: Responses were received from 209 programs (65%), of which 88% (n = 184) were hospital-based outpatient facilities. Most (91%, n = 190) programs described enrolling patients continuously, and 80% (n = 167) reported a wait time from referral to the initial PR visit of <4 wk. Organization-level strategies to increase referral to PR included active surveillance (48%, n = 100) and COPD-focused staff (49%, n = 102). Provider-level strategies included clinician education (45%, n = 94), provider outreach (43%, n = 89), order sets (45%, n = 93), and automated referrals (23%, n = 48). Patient-level strategies included bedside education (53%, n = 111), flyers (49%, n = 103), motivational interviewing (33%, n = 69), financial counseling (64%, n = 134), and transportation assistance (35%, n = 73). Fewer than one-quarter (18%, n = 38) of PR programs reported using both bedside education and automatic referral, and 42% (n = 88) programs did not use either strategy. Conclusions: This study describes current practices in the United States, and highlights opportunities for improvement at the organization, provider, and patient level. Future research needs to demonstrate the effectiveness of these strategies, alone or in combination.